Mediterranean diet and structural neuroimaging biomarkers of Alzheimer's and cerebrovascular disease: a systematic review. (20th December 2022) - Gregory, Sarah; Ritchie, Craig W.; Pullen, Hannah; Shannon, Oliver; Stevenson, Emma; Muniz‐Terrera, Graciela
Abstract: Background: Adherence to the Mediterranean diet (MedDiet) has been associated with better cognitive performance, lower incidence of dementia, stroke and lower Alzheimer's disease (AD) biomarker burden (Scarmeas et al, 2018). Improving dietary patterns in at‐risk populations may improve brain health, reducing incidence of dementia and stroke (Lewis et al, 2014; Feigin et al, 2019). The aim of this systematic review was to evaluate the evidence base for the MedDiet in relation to hippocampal volume and white matter hyperintensity volume (WMHV) (PROSPERO Registration: CRD42021269620). Method: We systematically searched for studies on MedDiet and hippocampal volume or WMHV in MedLine, EMBASE, CINAHL and PsycInfo. The review was carried out in line with PRISMA methodology. We included studies with adult participants in any setting, time or language. Searches were initially carried out between 21 st July 2021 and 19 th August 2021. Papers were screened independently by two authors against eligibility criteria. Data on participant demographics, MedDiet calculation and adherence, hippocampal volume and/or WMHV was extracted and narratively synthesised. Result: Of an initial 112 papers identified, six papers, enrolling 21, 750 participants, were eligible for inclusion in the review. The mean age of participants in studies ranged from 53.8 years to 80.3 years and participants were healthy volunteers, had subjective cognitive decline, or dementia. All studies included in the review were cross‐sectional or cohort studies. Four studies reported on hippocampal volume, with inconclusive or no associations seen with MedDiet adherence. One study found a significant association between higher MedDiet adherence and lower WMHV, while two other studies found no significant associations. Conclusion: Overall, these results highlight a gap in our knowledge about the associations between MedDiet and AD and cerebrovascular related structural neuroimaging findings. Future research is needed including increased frequency of dietary assessments, more sensitive and specific imaging outcomes and the inclusion of data from low‐ and middle‐income countries.